The scientific legacy of Harold Edwin Hurst (1880–1978). Issue 9 (3rd July 2016) - O'Connell, P.E.; Koutsoyiannis, D.; Lins, H. F.; Markonis, Y.; Montanari, A.; Cohn, T.
ABSTRACT: Emanating from his remarkable characterization of long-term variability in geophysical records in the early 1950s, Hurst's scientific legacy to hydrology and other disciplines is explored. A statistical explanation of the so-called "Hurst Phenomenon" did not emerge until 1968 when Mandelbrot and co-authors proposed fractional Gaussian noise based on the hypothesis of infinite memory. A vibrant hydrological literature ensued where alternative modelling representations were explored and debated, e.g. ARMA models, the Broken Line model, shifting mean models with no memory, FARIMA models, and Hurst-Kolmogorov dynamics, acknowledging a link with the work of Kolmogorov in 1940. The diffusion of Hurst's work beyond hydrology is summarized by discipline and citations, showing that he arguably has the largest scientific footprint of any hydrologist in the last century. Its particular relevance to the modelling of long-term climatic variability in the era of climate change is discussed. Links to various long-term modes of variability in the climate system, driven by fluctuations in sea surface temperatures and ocean dynamics, are explored. Several issues related to the Hurst Phenomenon in hydrology remain as a challenge for future research.Editor M. Acreman;Associate editor A. Carsteanu